Perlindungan Hukum terhadap Tagihan Piutang Kreditur yang Tertolak Pada Tahapan Verifikasi oleh Pengurus dalam Proses PKPU - Faisalsyah, Moch Akbar Alfian; Nasution , Krisnadi (CV. Era Digital Nusantara, 2024)
This research aims to analyze the legal protection of creditor receivables that are rejected at the verification stage by the management in the PKPU process. The type of research used in this research is normative legal research, and also uses 2 (two) approaches, namely the statute approach and conceptual approach. The results of this study show that the consideration of the Panel of Judges in deciding cases based on the Constitutional Court Decision Number 23/PUU-XIX/2021 has reflected the principle of justice as a grant of rights to members of society based on the principle of proportional equality and the principle of justice enshrined in the Bankruptcy and PKPU Law. Debtors and their respective creditors can defend their respective rights in the context of debt settlement through the cassation legal remedy mechanism. The legal implications of the Constitutional Court Decision Number 23/PUU-XIX/2021 on PKPU as a form of debt settlement with a fast dimension can be reviewed from the characteristics of PKPU which make the process time period increase due to the cassation appeal that can be filed; and the open cassation appeal is a strategic effort to realize the right justice paying attention to accuracy and accuracy in terms of the principle of fast and simple justice. Additional costs for the cassation appeal are a logical consequence for the implementation of the case.